Investigation of the Electronic Structure of Transition Metal-Ions in Solution from Aqua-Complexes to Porphyrins : Untersuchung der Elektronischen Struktur von Übergangsmetall-Ionen in Lösung, vom aqua-Komplex zu Porphyrinen - Golnak, Ronny (Freie Universität Berlin, 2017)
1 Introduction 1.1 Porphyrins Role in Nature 1.2 The Study of Solvated Porphyrins 1.3 Brief Introduction of the Thesis Content 2 Experimental and Theoretical Methods 2.1 X-ray Spectroscopies 2.1.1 X-ray Interaction with Matter 2.1.2 X-ray Absorption Coefficients and Cross-Sections 2.1.3 Radiative and Non-Radiative Decays 2.1.4 X-ray Absorption Spectroscopy (XAS) 2.1.5 X-ray Emission Spectroscopy (XES) 2.1.6 Resonant Photoelectron Spectroscopy (RPES) 2.2 Experimental Methods and Setups 2.2.1 Synchrotron Facility - BESSY II 2.2.2 Beamline - U41-PGM 2.2.3 Experimental Station - LiXEdrom 2.2.4 Liquid in Vacuum - Micro-Jet 2.2.5 Liquid in Vacuum - Flow Cell 2.3 Sample Preparation and Measurement Considerations 2.3.1 Aqueous Ferric Solution 2.3.2 Aqueous Ferrous Solution 2.3.3 FePPIX-Cl in DMSO 2.3.4 CoPPIX-Cl in DMSO 2.3.5 FePPIX- Cl in NaOH 2.3.6 MnOEP-Cl and MnTPP-Cl in DCM 2.3.7 FeOEP-Cl and FeTPP-Cl in DCM 2.4 Theoretical Modeling - ORCA Program Package 2.4.1 [Fe(H2O)6]3+ Complex 2.4.2 [Fe(H2O)6]2+ Complex (MOLCAS 8.0) 2.4.3 Porphyrin Complexes 3 Iron Chlorides in Aqueous Solution - a Simple Model System 3.1 Undistorted XAS Probed by Core-Level Emission 3.2 Metal-Ligand Interactions Revealed by Combined Probing of RIXS and RPES 4 Metalloporphyrins in Solution - a Complex System 4.1 Solvated Metalloporphyrin Monomers 4.1.1 FePPIX-Cl in DMSO 4.1.2 CoPPIX-Cl in DMSO 4.2 Intermolecular Interactions in FePPIX-Cl Dimer 4.2.1 Local Energy Gap Opening at the Iron Site 4.2.2 Characteristic XA-Feature Shifting of Nitrogen 4.3 Outer Ligand Effects on Metalloporphyrins in Solution 4.3.1 Outer Ligand Effect on the Metal Center 4.3.2 Metal-Solvent Interaction Assisted by Porphyrin Outer Ligands 5 Summary and Outlook : This thesis reports how, by the development of the vacuum liquid micro-jet technique as well as the flow cell technique for soft X-ray spectroscopy, electronic structure measurements on liquid have advanced to date. My focus is on investigations of solvated transition metals in both simple and complex systems. These transition metal systems are at the heart of current research activities world-wide, in fields including physical chemistry and biology, and aiming at a molecular level to the understanding of the interactions of metal- ligand and metal-solvent. For the transition metal aqueous solutions (simple system) I have systematically compared all possible decay channels upon resonant excitation at the Fe L-edge, including radiative fluorescence yield and non-radiative electron yield both for valence and core-level emissions, in order to discover an undistorted detection method for XAS measurements. Our analysis suggests a new protocol for investigation of X-ray spectra and its implications for the study of transition metal solute-solvent electronic interactions, being important to promote our understanding of the geometric and electronic structure and the rational design of catalytic and functional materials. For complex systems the local electronic structure of hemin has been investigated first by X-ray absorption and emission spectroscopy at the Fe L-edge and N K-edge. The study was performed for hemin in aqueous solution where dimerization occurs and in organic solution where the molecule remains monomer. A local energy gap at the Fe sites was observed for the hemin dimer, with the occupied valence states shifted to lower binding energies, while the unoccupied valence states share the same energies as the hemin monomer. In addition, solute-solvent electronic structure interactions of porphyrin at very low concentrations in liquid solution are presented. For Mn- tetraphenylporphyrin chloride and Mn-octaethylporphyrin chloride distinctive spectral features of metal-to-ligand charge-transfer were observed, when characterized by resonant inelastic X-ray scattering at the Mn L-edge and N K-edge. In the case of Fe-octaethylporphyrin chloride and Fe- tetraphenylporphyrin chloride, it is argued that the Fe center of the Fe octaethylporphyrin is more capable of binding small solvent molecules, than the tetraphenylporphyrin complex in solution. The proposed binding mechanism is through the assistance of the dipole interaction between the porphyrin- ligand system and the solvent molecule, in a situation where the ligand structure and arrangement maximize the binding interactions. Our studies demonstrate that even small ligands, depending on their structure and arrangement, can have considerable effects on the porphyrin metal center chemistry in liquid solution. All studies at the porphyrin complexes are accompanied by the interpretation of density functional theory with restricted open-shell configuration interaction singles (DFT/ROCIS) calculations. : Die vorliegenden, im Rahmen meiner Doktorarbeit durchgeführten Untersuchungen zeigen, wie sich die Röntgenspektroskopie im weichen Röntgenbereich zur Analyse der elektronischen Struktur in Lösung, mittels Mikroflüssigkeitsstrahl und Durchflusszelle im Vakuum, weiterentwickelt hat. Der Fokus meiner Untersuchungen liegt auf gelöste Übergangsmetall-systeme mit sowohl einfachem als auch komplexerem Aufbau. Diese Komplexe sind Gegenstand aktueller, weltweiter wissenschaftlicher Forschungsfelder, wie der physikalischen Chemie und der Biologie. Bei den relativ einfach aufgebauten Übergansmetall-Wasser- Komplexen in Lösung, erfolgte ein systematischer Vergleich sämtlicher elektronischer Wechselwirkungsprozesse, ausgelöst durch resonante Anregung an der Eisen L-Kante. Der Vergleich basiert auf Messungen mittels partieller Fluoreszenzausbeute- und Elektronenausbeutetechniken. Das Ziel ist es, eine Detektionsmethode zu etablieren, die ein störungsfreies Röntgenabsorptionsspektrum (XAS) liefert. Unsere Ergebnisse sind bedeutend für die Interpretation von Röntgenspektren und fördern das Verständnis von elektronischen Wechselwirkungen zwischen den gelösten Komplexen und dem umgebenden Lösungsmittel in katalytischen und funktionalen Materialien. Als komplexeres System wurde zuerst die elektronische Struktur von Hemin in Lösung mittels XAS und XES an der Eisen L-Kante sowie der Stickstoff K-Kante untersucht. Dabei wurde das Molekül als Dimer in wässriger Lösung und als Monomer in organischer Lösung (DMSO) analysiert und verglichen. Für das Dimer wurde eine Energielücke in Valenzzuständen gefunden, wobei die besetzten Valenzzustände zu niedrigeren Energien verschoben sind, während die unbesetzten Valenzzustände die gleichen Energien wie das Monomer des Hemins aufweisen. Zusätzlich werden die Solvat-Solvens-Wechselwirkungen in der elektronischen Struktur von weiteren Porphyrinen bei niedrigen Konzentrationen in Dichlormethan vorgestellt. Die Charakterisierung mittels resonanter unelastischer Röntgenstreuung an der Mangan L-Kante und der Stickstoff K-Kante liefert markante spektrale Kennzeichen für Metall-zu-Liganden-Ladungstransfer in Tetraphenyl- und Oktaethylporphyrinen des Mn(III). Im Fall von Tetraphenyl- und Oktaethyl-porphyrin des Fe(III) tritt eine Interaktion mit den Lösemittelmolekülen auf, welche für den Oktaethylkomplex stärker ausfällt. Der vorgeschlagene Bindungsmechanismus wird dabei von Dipolwechselwirkungen des Porphyrinsystems und den Lösemittelmolekülen gesteuert, wobei die sterische Anordnung der Alkylgruppen des Porphyrins diesen Vorgang begünstigt. Unsere Untersuchungen zeigen somit, dass bereits die Variation in kleinen funktionellen Gruppen des Porphyrinliganden einen messbaren Effekt auf die elektronische Struktur des Metallzentrums in Lösung haben kann. Sämtliche Untersuchungen an Porphyrinen wurden durch die Auswertung theoretischer Berechnungen (DFT/ROCIS) begleitet.